Inability of Low Oxygen Tension to Induce Chondrogenesis in Human Infrapatellar Fat Pad Mesenchymal Stem Cells - Rahman, Samia; Szojka, Alexander R. A.; Liang, Yan; Kunze, Melanie; Goncalves, Victoria; Mulet-Sierra, Aillette; Jomha, Nadr M.; Adesida, Adetola B. (Frontiers in Cell and Developmental Biology, 2021)
Objective: Articular cartilage of the knee joint is avascular, exists under a low oxygen tension microenvironment and does not self-heal when injured. Human infrapatellar fat pad sourced mesenchymal stem cells (IFP-MSC) are an arthroscopically accessible source of MSC for the repair of articular cartilage defects. Human IFP-MSC exist physiologically under a low oxygen tension (i.e., 1-5%) microenvironment. Human bone marrow mesenchymal stem cells (BM-MSC) exist physiologically within a similar range of oxygen tension. A low oxygen tension of 2% spontaneously induced chondrogenesis in micromass pellets of human BM-MSC. However, this is yet to be demonstrated in human IFP-MSC or other adipose tissue sourced MSC. In this study, we explored the potential of low oxygen tension at 2% to drive the in vitro chondrogenesis of IFP-MSC. We hypothesized that 2% O2 will induce stable chondrogenesis in human IFP-MSC without the risk of undergoing endochondral ossification at ectopic sites of implantation. Methods: Micromass pellets of human IFP-MSC were cultured under 2% O2 or 21% O2 (normal atmosphere O2) in the presence or absence of chondrogenic medium with transforming growth factor-beta 3 (TGF-beta 3) for 3 weeks. Following in vitro chondrogenesis, the resulting pellets were implanted in immunodeficient athymic nude mice for 3 weeks. Results: A low oxygen tension of 2% was unable to induce chondrogenesis in human IFP-MSC. In contrast, chondrogenic medium with TGF-beta 3 induced in vitro chondrogenesis. All pellets were devoid of any evidence of undergoing endochondral ossification after subcutaneous implantation in athymic mice.